2018
DOI: 10.18632/oncotarget.24345
|View full text |Cite
|
Sign up to set email alerts
|

Pumilio2regulates synaptic plasticity via translational repression of synaptic receptors in mice

Abstract: PUMILIO 2 (PUM2) is a member of Pumilio and FBF (PUF) family, an RNA binding protein family with phylogenetically conserved roles in germ cell development. The Drosophila Pumilio homolog is also required for dendrite morphogenesis and synaptic function via translational control of synaptic proteins, such as glutamate receptors, and recent mammalian studies demonstrated a similar role in neuronal culture with associated motor and memory abnormalities in vivo. Importantly, transgenic mice with PUM2 knockout show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…As outlined above, Pum2 and Stau2 exert distinct roles in this process. It was shown that Pum2 represses expression of sodium channels, such as Na v 1.6 (Driscoll et al, 2013), as well as the AMPA receptor subunit Gria2 in the hippocampus (Dong et al, 2018), thereby dampening neuronal excitation. In our study, we do not observe Gria2 being regulated by Pum2.…”
Section: Gabaergic Transmission Depends On Pum2mentioning
confidence: 99%
“…As outlined above, Pum2 and Stau2 exert distinct roles in this process. It was shown that Pum2 represses expression of sodium channels, such as Na v 1.6 (Driscoll et al, 2013), as well as the AMPA receptor subunit Gria2 in the hippocampus (Dong et al, 2018), thereby dampening neuronal excitation. In our study, we do not observe Gria2 being regulated by Pum2.…”
Section: Gabaergic Transmission Depends On Pum2mentioning
confidence: 99%
“…Human PUM1 and PUM2 are expressed across tissues and their expression is highly overlapping [5,16] suggesting that they likely act redundantly. Mammalian PUM proteins have been implicated in spermatogenesis [17,18], neuronal development and function [19][20][21][22][23][24], immune function [25,26], and cancer [27][28][29][30]. PUM1 missense and deletion mutants lead to adult-onset ataxia (Pumilio1-related cerebellar ataxia, PRCA) and loss of one copy leads to developmental delay and seizures (Pumilio1-associated developmental disability, ataxia, and seizure; PADDAS) [31].…”
Section: Introductionmentioning
confidence: 99%
“…Inset shows an example Western Blot. ** = p < 0 .01, *** = p < 0.001 Validated Pum-dependent regulated transcripts, in mammals, include Nav1.1 (SCN1A), Nav1.6 (SCN8A) and GLUR2 (aka GLUR-A, AMPA receptor) 2,8,21 . Bioinformatic analysis of expressed mRNAs also identifies a putative PRE motif in NaV1.2 (SCN2A), indicative that this channel variant is also regulated by Pum 12 .…”
Section: -Tbb Reduces Induced Ptz-induced Seizure In Micementioning
confidence: 99%
“…However, Pum requires additional co-factors (including Nanos and Brain-tumor) and the actual effect of Pum is likely dictated by both the number and proximity of these additional binding elements, in addition to the number of PREs 6,7 . In mammals, regulated transcripts that have potential to influence neuron activity include Na v 1.6 (SCN8A) 2 and GLUR2 (AMPA receptor) 8 . Pum-dependent homeostatic translational repression of Na v 1.6, in rat cortical pyramidal neurons, reduces the amplitude of expressed voltage-gated Na + current (I Na ) and lowers action potential firing frequency 2 .…”
Section: Introductionmentioning
confidence: 99%